Analysis of consumers' attitudinal and emotional factors on luxury apparel brand purchase intentions. Issue 11 (10th September 2019) - Wang, Stephen W.; Pelton, Lou E.; Hsu, Maxwell K.
ABSTRACT: This study advances both descriptive and managerial research addressing foreign consumers' attitudinal, attributional and emotional valuations of brand equity for a U.S.-based global luxury brand. Taiwan was selected as the focal population of interest because this foreign market is distinguished by high market penetration and consumer awareness of global apparel brands. Consistent with a call for additional research on this topic, the present study employed both qualitative and quantitative research methods to empirically assess the relationship of foreign consumers' brand awareness, attitudinal and emotional factors with the ensuing purchase intentions. Notably, customers' level of price sensitivity is also included in the model, and the empirical findings reveal that price sensitivity negatively influences purchase intentions. The results also suggest that consumers' susceptibility for perceived quality has a positive influence on purchase intentions for the U.S. apparel brand through emotional value. The takeaway for marketers in the luxury apparel industry is to increase the brand value in the customers' mind to offset the likely negative effect of consumer price sensitivity. In addition, fashion brand managers could consider penetrating the brand-sensitive buyer's market with a popular name brand and try to exploit the brand-insensitive buyer market with a generic apparel brand.